Unveiling Dynamics in Nanostores: An Extensive Meta-Analysis of the Interplay of Supply Chain Integration and Operational Performance - Ortega-Jimenez, Cesar Humberto; Mohmmad Alhusban, Abdallah Omar (LACCEI, 2023)
Abstract– The purpose of this paper is to explore the intricate interplay between supply chain integration and the operational performance of Nanostores. This study synthesizes eight previous studies to determine the dynamics and correlations that affect these establishments’ performance. This meta-analytical study examines sales revenue, customer footfall, and customer satisfaction. The paper uses a systematic review of literature to explain the complex relationship between supply chain integration and operational success. The meta-analysis shows that Nanostores with effective supply chain integration perform better. The study emphasizes the importance of inventory management, supplier relationships, order fulfillment, demand forecasting, logistics and distribution, technology adoption, and returns and reverse logistics in Nanostore operations. This research consolidates and analyzes existing studies to provide valuable insights, but it acknowledges literature limitations. Nanostores are constantly changing, so future research could examine new supply chain strategies and trends to better understand their operations. This study may change society’s view of small-scale retailers and their economic impact. The study may spark Nanostore support mechanism discussions, boosting local economies and community development by highlighting supply chain integration’s importance. This paper combines research to reveal how supply chain integration affects Nanostore operational performance. The study’s unique focus on this specialized sector helps understand retail’s challenges and opportunities, enabling better practices and decision-making.